Some effects on the efficient frontier of the investment strategy: A preliminary approach - Méndez-Rodríguez, Paz; García-Bernabeu, Ana; Hilario, Adolfo; Pérez-Gladish, Blanca (Revista Electrónica de Comunicaciones y Trabajos de ASEPUMA, 2013)
In this work an indicator of the social responsibility degree of mutual funds is proposed based on the mutual fund’s screening policy and on the quality of the information provided by the fund manager. Once this indicator is obtained it is included as a constraint in the mean-variance classical optimization model. An exploratory numerical experiment is presented in order to check the possible effect on the efficient frontier of different SRI strategies.